2007
DOI: 10.2174/156720207782446379
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine and Olanzapine but not Risperidone Impair the Pre-Frontal Striatal System in relation to Egocentric Spatial Orientation in a Y-Maze

Abstract: Many studies indicate a dissociation between two forms of orientation: allocentric orientation, in which an organism orients on the basis of cues external to the organism, and egocentric spatial orientation (ESO) by which an organism orients on the basis of proprioceptive information. While allocentric orientation is mediated primarily by the hippocampus and its afferent and efferent connections, ESO is mediated by the prefronto-striatal system. Striatal lesions as well as classical neuroleptics, which block d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In fact, several authors argue that APDs may worsen cognition, particularly typical first generation APDs (Kasper and Resinger, 2003; Woodward et al, 2007). Similar findings have been reported in rodent studies, with either no effect (Kamei et al, 2006), or impaired working and recognition memory following olanzapine and clozapine administration (Addy and Levin, 2002; Castro et al, 2007; Levin and Christopher, 2006; Levin et al, 2005; Ortega-Alvaro et al, 2006). On the contrary, olanzapine, clozapine and ziprasidone attenuate cognitive deficits following phencyclidine and MK-801 treatment in rodents (Abdul-Monim et al, 2006; Karasawa et al, 2008).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In fact, several authors argue that APDs may worsen cognition, particularly typical first generation APDs (Kasper and Resinger, 2003; Woodward et al, 2007). Similar findings have been reported in rodent studies, with either no effect (Kamei et al, 2006), or impaired working and recognition memory following olanzapine and clozapine administration (Addy and Levin, 2002; Castro et al, 2007; Levin and Christopher, 2006; Levin et al, 2005; Ortega-Alvaro et al, 2006). On the contrary, olanzapine, clozapine and ziprasidone attenuate cognitive deficits following phencyclidine and MK-801 treatment in rodents (Abdul-Monim et al, 2006; Karasawa et al, 2008).…”
Section: Introductionsupporting
confidence: 88%
“…On the other hand, APDs olanzapine and risperidone exacerbated deficits in spatial working memory and attention during the Oculomotor Delayed Response task (Reilly et al, 2007) and decreased dorsolateral prefrontal cortex activation during motor learning tasks (Keedy et al, 2015) in previously APD-naïve schizophrenia patients after 4-6 weeks of treatment. In rodents, olanzapine impaired working memory during Y-Maze and Eight-Arm Radial Maze tests (Castro et al, 2007; Levin et al, 2005; Ortega-Alvaro et al, 2006), and reduced memory acquisition and retrieval in mice during the modified Elevated Plus Maze task (Mutlu et al, 2011). Clinically, APDs can cause varying degrees of sedation (Leucht et al, 2009) and it is possible that sedation impacted the cognitive data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PrP C acts as a receptor for the laminin γ‐1 chain and the transmembrane protein neuronal cell adhesion molecule (NCAM), which mediates neuronal adhesion and neurite outgrowth [19,20,22]. In vivo studies showed that interactions of PrP C with laminin γ‐1 chain or the Stress Inducible Protein 1 (STI1), another PrP C ligand, are involved with memory consolidation [23,24].…”
Section: Introductionmentioning
confidence: 99%